2022
DOI: 10.1590/1809-4430-eng.agric.v42n1e20210112/2022
|View full text |Cite
|
Sign up to set email alerts
|

DRYING CHARACTERISTICS AND QUALITY ANALYSIS OF HOT AIR-ASSISTED RADIO FREQUENCY AND HOT-AIR DRYING OF JUJUBE ( Zizyphus jujube Miller cv. Jinsixiaozao )

Abstract: Radio frequency (RF) drying is a rapid dehydration technique that reduces water activity and extends the shelf life of agricultural products. In this study, the drying characteristics of jujube during HARF and hot air (HA) were investigated, and quality analyses, such as color, vitamin C (VC) and total flavonoid content (TFC), of jujube were performed. The drying curves revealed that the drying time used to reduce the moisture content from 81.7 to 6.0% on a dry basis was 360 and 1320 min using HARF drying and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The product storage factors, such as temperature and duration, also have a significant role in the reduction of bioactive compound levels in jujube fruit extract. TPC and TFC levels decreased faster at higher product storage temperatures and longer duration of product storage [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The product storage factors, such as temperature and duration, also have a significant role in the reduction of bioactive compound levels in jujube fruit extract. TPC and TFC levels decreased faster at higher product storage temperatures and longer duration of product storage [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the investigation of drying characteristics of inshell hazelnuts dried by combined radio frequency (RF) and hot air (HA), the results showed that when RF heating was applied during or before HA drying, energy efficiency, drying efficacy, and nut quality were enhanced, the anisidine content is higher than the HA ones [9]. As for the jujube, a recent study showed that compared with HA drying, HARF drying showed a shorter drying time, higher drying efficiency and better product quality, that is, higher vitamin C content, smaller color difference and higher total flavonoid content [10].…”
Section: Introductionmentioning
confidence: 99%